Narratives of Inclusion: Story-Based Reflections on Special Education Practices in Finnish Primary Schools - Juha Laaksonen; Heidi Korhonen; Antti Vainio (Yayasan Adra Karima Hubbi, 2025)
Background. Inclusive education in Finland has long been recognized as a global model for equity and student-centered practices. However, less is known about the lived experiences of teachers, students, and families within these systems. Purpose. This study aims to explore the dynamics of inclusion in Finnish primary schools through narrative inquiry, focusing on story-based reflections that illuminate the practical realities of special education implementation. Method. Using a qualitative approach, we conducted in-depth interviews and collected reflective journals from 12 educators and 5 special education coordinators across three municipalities in Finland. The narratives were analyzed thematically to uncover both enabling conditions and challenges in daily inclusive practices. Results. Findings reveal a strong commitment to inclusion supported by multi-tiered systems of support (MTSS), yet tensions remain in workload management, inter-professional collaboration, and cultural diversity responsiveness. Participants’ stories underscore the importance of empathy, flexibility, and sustained professional development in cultivating inclusive classrooms. Conclusion. This study contributes to the broader discourse on inclusive education by emphasizing the role of personal and professional storytelling as a medium for reflective practice and policy insight. The research highlights the significance of listening to practitioners’ voices in shaping meaningful, context-sensitive inclusive education strategies.